Warrant Pricing: Jump-Diffusion vs. Black-Scholes - Kremer, Joseph W.; Roenfeldt, Rodney L. (Journal of Financial and Quantitative Analysis, 1993)
This paper investigates the warrant pricing abilities of dilution-adjusted versions of the Black-Scholes and Jump-Diffusion option pricing models. Because of the typically long lives of warrants, their pricing is hypothesized to benefit from use of the Jump-Diffusion model, which relaxes the Black-Scholes restriction against stock price jumps. Empirical results indicate that while the Black-Scholes model almost uniformly provides more efficient estimates, the Jump-Diffusion model generally provides less biased estimates of market value. Particularly for the valuation of out-of-the-money warrants and warrants on stocks with a history of large and/or frequent jumps, the Jump-Diffusion model may be preferred.